Birds reported to Birdline, but not reported to IBL - Fuller, James L.et al (1991)
A list of bird sightings reported to Iowa Birdline, but not submitted to Iowa Bird Life compiled by James Fuller. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of spring 1991. Epson - sheet feed/flatbed